IDENTIFIKASI RISIKO DAN PERMASALAHAN PADA PEMBANGUNAN JEMBATAN KERETA API ELEVETED TRACK SIMPANG JOGLO - Puspitasari, Nikmatul Rochmy; Wibowo, Kartono; Mudiyono, Rachmat (Jurnal Teknik Sipil Giratory UPGRIS, 2024)
The construction of the Simpang Joglo Elevated Track Bridge is an iconic development in the city of Surakarta with the Elevated Railway Bridge which was built over seven very busy intersections. At this intersection, traffic jams often occur when trains pass, for this reason an elevated track railway bridge was built to reduce this congestion. The implementation of development is not free from risks that occur both internally and externally. This research aims to identify the risks and problems that occur in the construction of the Simpang Joglo Elevated Track Bridge. After identification, an assessment will be carried out on the level of risk that has been identified in the construction of the elevated track bridge at Joglo intersection. Data collection was divided into two, namely primary data collection through distributing questionnaires and interviews on the Simpang Joglo Elevated Track Bridge Construction Project which was conducted with project owners, consultants and contractors and secondary data collection through previous research and data from the Simpang Joglo Elevated Track Bridge Construction Project. Risk identification is carried out using the Risk Breakdown Structure (RBS) method and probability impact grid to determine the level of risk. After obtaining the data, a feasibility test will be carried out on respondents and then a validity and reliability test will be carried out for the three stakeholders. Risk identification is carried out by calculating the probability and impact for each variable and then clarifying the ranking using the Extremely Ineffective, Ineffective, Moderately Ineffective, Very Effective and Extremely Effective rating scale. After that, the risk level is classified using a probability-impact matrix. From the results of the risk level classification, it was found that there were 31 risk variables in the high category from the owner, 31 risk variables according to the consultant and 19 risk variables according to the contractor. Determining the high category of risk is based on combining the same variables from the three stakeholders to obtain 18 risk variables. These variables are problems that occur and influence the implementation of the Simpang Joglo Elevated Track Bridge Construction Project. These problems include increased vibration, traffic flow, road damage, K3 environmental sanitation, community attitudes and perceptions, organizational structure, payments, owner finances, overtime, time and cost estimates, changes in design, heavy equipment and materials